2013
DOI: 10.1242/jeb.089219
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific ionomotive enzyme activity and K+ reabsorption reveal the rectum as an important ionoregulatory organ in larvalChironomous ripariusexposed to varying salinity

Abstract: Summary A role for the rectum in the ionoregulatory homeostasis of larval Chironomus riparius was revealed by rearing animals in different saline environments and examining: (1) the spatial distribution and activity of keystone ionomotive enzymes Na+-K+-ATPase (NKA) and V-type H+-ATPase (VA) in the alimentary canal and (2) rectal K+ transport with scanning ion-selective electrode technique (SIET). NKA and VA activity were measured in four distinct regions of the alimentary canal as follows: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 70 publications
(82 reference statements)
2
34
0
Order By: Relevance
“…The rectum of larval C. riparius is a site of K + absorption (see Jonusaite et al, 2013). The mean baseline K + flux (absorption, lumen to bath) measured at the recta in this study was 104.3±13.7 pmol cm −2 s −1 (n=38).…”
Section: The Journal Of Experimental Biologymentioning
confidence: 59%
See 4 more Smart Citations
“…The rectum of larval C. riparius is a site of K + absorption (see Jonusaite et al, 2013). The mean baseline K + flux (absorption, lumen to bath) measured at the recta in this study was 104.3±13.7 pmol cm −2 s −1 (n=38).…”
Section: The Journal Of Experimental Biologymentioning
confidence: 59%
“…Therefore, salinity and AST7 have similar effects on rectal NKA and VA activities. The actions of AST7 occur rapidly and hence cannot be mediated by changes in NKA and VA expression; however, it was suggested that larvae reared in brackish water may have lower expression of rectal NKA and VA than those reared in freshwater (Jonusaite et al, 2013). In an effort to determine whether the mechanisms of AST7-and salinity-induced changes in NKA and VA rectal activities are similar or different, NKA and VA protein expression studies on freshwaterand brackish-water-reared larvae were carried out.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
See 3 more Smart Citations